(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث بعضاً من عوامل التحول الديمغرافي، وبخاصة ما تلعبه الوفاة من أثر على الخصوبة، لأن انخفاضها إلى الحدود الدنيا في أغلب بلدان العالم كان السبب المباشر للنمو السكاني السريع، حيث يعود هذا الانخفاض في الوفاة إلى استجابة الإنسان للثورة الصحية التي عمت أرجاء المعمورة وإلى مساعي منظمة الصحة العالمية في الحثّ على تفعيلها في بلدان هذه المعمورة من خلال ما تقدمه من مساعدات وإعانات مادية وبشرية للتخفيف من حدة الأمراض السارية وانتشارها، كما تُعد الخصوبة منظمة ذاتياً لحد ما، لأن النظريات الاقتصادية تقر بأن الناس لديهم رغبات متعلقة بحجم أسرهم، حيث إنّهم يسعون بأشكال مختلفة من السلوك مكافئة لإرضاء أهدافهم تقريباً، وعليه يمكن للخصوبة أن تقترب من التكيف لخدمة الفرد أو أنها أنموذج إضافي لطلب الأسرة. وقد حاولنا في هذا البحث، رصد انعكاسات الأثر المتوقع لمّا بعد التحول الديمغرافي على الصحة الإنجابية وسلوك الأفراد الإنجابي، كي يتجلى بما يُعرف " بالكسب الديمغرافي ". This research addresses some of the factors of demographic transformation, especially the effect of death on fertility; its being decreased to a minimum in most countries of the world is the direct cause of rapid population growth; this decrease is attributed to human response to the health revolution that pervaded the globe and to the WHO efforts in pushing for activating it worldwide through its financial and human aid in order to alleviate the prevalence of epidemic diseases. Fertility is considered self-regulating, since economic theories state that people have desires for the size of their families in that they seek various forms of behavior that meet their ends. Therefore, fertility could be close to adaptation by way of serving the individual, or it might be seen as an additional model for family demand. We have tried in this research to monitor the reflections of the expected impact of post-demographic transformation on reproductive health and reproductive behavior of individuals represented in what is known as "demographic gain" .